Blickfeld : Kunst in Gera - Teil 1. - Badstübner-Gröger, Sibylle; Beer, Christoph; Bohn, Angelika; Buchholz, Erik; Jakobson, Hans-Peter; Oehler, Peter; Pesl, Kurt; Rauch, Ralf; Rüdiger, Frank; Rüdiger, Ulrike; Saupe, Holger Peter; Scheler, Ute; et al. (Gera : Stadt Gera, 2000)
Beer, Christoph ; Buchholz, Erik ; Dietzsch, Eberhard ; Fischer, Ulrich ; Frotzscher, Frank ; Lechner, Barbara ; Lehmann, Bernd ; Lepke, Gerda ; Lüttich, Christian ; Oehler, Peter ; Reinhöfer, Uwe ; Rüdiger, Frank ; Schenke, Angelika ; Schenke, Frank ; Schmidt, Sven ; Schulze, Joachim B. ; Schwarzentrub, Wolfgang ; Schütt, Katja ; Toch, Barbara ; Voigtmann, Kay
biografie
Blickfeld : Kunst in Gera - Teil 1, Sommerausstellung 2000 in Gera
Duits
boek
Keywords: Gera